Pengaruh Value Added Intellectual Capital Terhadap Produktivitas Karyawan dan Return on Asset Pada Perusahaan Jasa yang Terdaftar di BEI - Jessica, Ariyanti (Business Accounting Review, 2015)
The purpose of this study was to examine the influence of value added intellectual capital (VAIC) on employeeâs productivity and return on asset in service companies listed in Indonesian Stock Exchange. The motivation of this research was to provide clarity of the results from the previous researches. This study used 34 service companies that run in hospitality, restaurant and tourism, advertising, printing, and media, computer services, telecommunication, transportation, toll, airport, harbor, and the kind of, as well as non-building construction during 2008 until 2013. By using multiple linear regression, the results were VAIC had significant influence on employeeâs productivity and return on asset. From each component of VAIC, human capital efficiency (HCE) had negative significant influence on employeeâs productivity and had no significant impact on return on asset, while structural capital efficiency (SCE) and capital employed efficiency (CEE) had positive significant influence on both employeeâs productivity and return on asset.